A geometry problem by Ajay Sambhriya

Geometry Level 3

If A F = 1 AF=1 and A B = A C = 7 AB = AC = 7 , what is the radius of the grey circle?

25/8 25/6 25/12 25/9

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 23, 2017

Relevant wiki: Pythagorean Theorem

Flip the figure horizontally and let A A be the origin, A C AC along the x x -axis and A B AB along the y y -axis. Let D D be the center of the grey circle. We note that D E = r DE= r , the radius of the grey circle and that

A G = 7 A D + D G = 7 By Pythagorean theorem A E 2 + D E 2 + r = 7 d 2 + r 2 + r = 7 d 2 + r 2 = 7 r Squaring both sides d 2 + r 2 = 49 14 r + r 2 d 2 = 49 14 r \begin{aligned} AG & = 7 \\ {\color{#3D99F6}AD} + DG & = 7 & \small \color{#3D99F6} \text{By Pythagorean theorem} \\ {\color{#3D99F6}\sqrt{AE^2+DE^2}} + r & = 7 \\ \sqrt{d^2+r^2} + r & = 7 \\ \sqrt{d^2+r^2} & = 7 - r & \small \color{#3D99F6} \text{Squaring both sides} \\ d^2+r^2 & = 49-14r+r^2 \\ \implies d^2 & = 49-14r \end{aligned}

Note that the equation for the grey circle is:

( x d ) 2 + ( y r ) 2 = r 2 For point F ( 0 , 1 ) d 2 + ( 1 r ) 2 = r 2 Note that d 2 = 49 14 r 49 14 r + 1 2 r + r 2 = r 2 50 16 r = 0 r = 25 8 \begin{aligned} (x-d)^2 + (y-r)^2 & = r^2 & \small \color{#3D99F6} \text{For point }F(0,1) \\ {\color{#3D99F6}d^2} + (1-r)^2 & = r^2 & \small \color{#3D99F6} \text{Note that } d^2 = 49-14r \\ 49-14r + 1 - 2r + r^2 & = r^2 \\ 50-16r & = 0 \\ \implies r & = \boxed{\dfrac {25}8} \end{aligned}

How do you know that A A , D D , and G G are collinear?

Matthew Miller - 3 years, 7 months ago

Log in to reply

Both D G DG and A G AG is perpendicular to the tangent at G G .

Chew-Seong Cheong - 3 years, 7 months ago

Let A E = d |AE| = d , and let D E = r |DE| = r be the radius of the grey circle. With A A being the origin and A C AC lying on the x x -axis, the equation of this circle is then

( x + d ) 2 + ( y r ) 2 = r 2 (x + d)^{2} + (y - r)^{2} = r^{2} . Now as point F F lies on this circle and A F = 1 |AF| = 1 we have that ( 0 , 1 ) (0,1) satisfies this equation, i.e., that

( 0 + d ) 2 + ( 1 r ) 2 = r 2 d 2 + 1 2 r + r 2 = r 2 d = 2 r 1 (0 + d)^{2} + (1 - r)^{2} = r^{2} \Longrightarrow d^{2} + 1 - 2r + r^{2} = r^{2} \Longrightarrow d = \sqrt{2r - 1} .

Next, we note that A D AD extended will pass through the upper point P P of intersection between the grey circle and blue quarter-circle. Then as D P = r |DP| = r and A P = A B = 7 |AP| = |AB| = 7 we have that A D = A P D P = 7 r |AD| = |AP| - |DP| = 7 - r . Looking then at the right triangle Δ A E D \Delta AED , by the Pythagorean Theorem we have that

A D 2 = A E 2 + D E 2 ( 7 r ) 2 = d 2 + r 2 = 2 r 1 + r 2 49 14 r + r 2 = 2 r 1 + r 2 16 r = 50 r = 25 8 |AD|^{2} = |AE|^{2} + |DE|^{2} \Longrightarrow (7 - r)^{2} = d^{2} + r^{2} = 2r - 1 + r^{2} \Longrightarrow 49 - 14r + r^{2} = 2r - 1 + r^{2} \Longrightarrow 16r = 50 \Longrightarrow \boxed{r = \dfrac{25}{8}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...